Manufacturing Engineering and Technology - Kalpakjian S. Serope (Singapore, Pearson Education, 2014)
In preparing the seventh edition of this book, our goal continues to be to provide a comprehensive and state-of-the-art manufacturing engineering and technology textbook, with the additional aims of motivating and challenging students in studying this important engineering discipline. As in the previous editions, the book attempts to present a broad overview, emphasizing a largely qualitative coverage of the science, technology, and practice of manufacturing. We have included detailed descriptions of the fundamentals of manufacturing processes, operations, and the manufacturing enterprise. The book continues to address the various challenges and issues in modern manufacturing processes and operations, ranging from traditional topics such as casting, forming, machining, and joining processes, to advanced topics such as the fabrication of microelectronic devices and microelectromechanical systems and nanomanufacturing. The book provides numerous examples and case studies, as well as comprehensive and up-to-date coverage of all topics relevant to modern manufacturing, as a solid background for students as well as for professionals